The Accuracy Paradox: Unpacking the Limitations of Wearable Health Devices - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The Accuracy Paradox: Unpacking the Limitations of Wearable Health Devices The proliferation of wearable health devices—from smartwatches to fitness tra...
Keywords: Digital Health; Diagnostics; Healthcare Innovation; Medical Ethics; Patient Care